2003
DOI: 10.1034/j.1600-0528.2003.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries incidence in permanent first molars after discontinuation of a school‐based chlorhexidine‐thymol varnish program

Abstract: The cessation for 3 years of a 3-month program of chlorhexidine-thymol varnish applications resulted in a nonsignificant increase in the prevalence of dental caries in the permanent first molar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…2 Chlorhexidine remains the gold standard as an antiplaque and anti-gingivitis agent, 3 and its efficacy in caries prevention had been established in clinical trials. 4 Its molecule is symmetric, consisting of a hexamethylene bridge with terminal 4-chlorophenyl groups. 3 It has been shown that chlorhexidine has an affinity to bacteria, probably because of an interaction between the positively charged chlorhexidine molecule and negatively charged groups on the bacterial cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…2 Chlorhexidine remains the gold standard as an antiplaque and anti-gingivitis agent, 3 and its efficacy in caries prevention had been established in clinical trials. 4 Its molecule is symmetric, consisting of a hexamethylene bridge with terminal 4-chlorophenyl groups. 3 It has been shown that chlorhexidine has an affinity to bacteria, probably because of an interaction between the positively charged chlorhexidine molecule and negatively charged groups on the bacterial cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] According to these results, the application of chlorhexidine did not affect the μ TBS value significantly. However, the difference in μ TBS between the bonding agents was significant as follows: Clearfil S 3 Bond showed the highest μ TBS, followed by G-Bond and Xeno V. Xeno V had the lowest pH (pH < 2), followed by G-Bond (pH = 2.3), and Clearfil S 3 Bond (pH = 2.4). Low-pH self-etch adhesives have rather low bond strengths, particularly to dentin.…”
Section: Discussionmentioning
confidence: 96%
“…Low-pH self-etch adhesives have rather low bond strengths, particularly to dentin. 22 This may be why Clearfil S 3 Bond showed the highest μ TBS, followed by G-Bond and Xeno V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, relatively few studies have been focused on the long-term effect of CHX gel [Zickert et al, 1987] or on CHX varnish application [Baca et al, 2003]. The aim of the present investigation was therefore to follow-up our two earlier clinical studies on professional fl ossing with CHX gel treatment in preschool children and teenagers, in order to fi nd out whether the differences established at the end of the studies were maintained.…”
mentioning
confidence: 96%